The Case for Geographical Indication Protection of the Mozambique White Prawn - United Nations Conference on Trade; Development (United Nations, 2022)
This study analyses the Mozambique experience of protecting and promoting fisheries with an emphasis on exploring geographical indication (GI) protection for the white prawn of Mozambique. It is achieved through an in-depth review of data collected from local stakeholders, reports based on past technical support provided by the United Nations Conference on Trade and Development (UNCTAD), the literature on GIs, and international and regional treaties and reports, among others. Fishery products such as Mozambican prawns are highly recommended for GI certification, as they have high demand from both local and international consumers.